Neurotoxic Snake Bite Poisoning - Kakkar, Ankita; Kumar , Sushil (Journal of Indian Academy of Forensic Medicine, 2014)
Snake bite is a significant health problem in India, particularly in the rural regions of the country.  In general about 70% of bites are due to snakes which are not poisonous, of the rest, 15% are dry bites  and only15% cause envenomation. Venom is the saliva of snake ejected during the act of biting, from the  poison apparatus (the modified parotid glands). It can be, neurotoxic, vasculotoxic, or myotoxic in its  action. Neurotoxicity is a key feature of some envenoming, and there are many unanswered questions  regarding its manifestations. The polyvalent antisnake venom serum available in India is effective against  most common poisonous snakes. Therefore, a prompt diagnosis and timely administration of polyvalent  antisnake venom, in a case of snake bite can not only be life saving, but also prevent morbidity to a great  extent. Neurotoxic snakes for example common krait hunt nocturnally, and are quick to bite people  sleeping on the floor, often without waking their victims, since the venom is painless. Victims wake up  later, paralyzed or die in their sleep. In the present case report, we discuss the neurological manifestations, disease course and its  outcome in one such patient of snake bite.
Keywords: Envenomation; Mortality; Morbidity; Manifestations